A long‐term study examining the antibacterial effectiveness of Agion silver zeolite technology on door handles within a college campus. (19th December 2014) - Potter, B.A.; Lob, M.; Mercaldo, R.; Hetzler, A.; Kaistha, V.; Khan, H.; Kingston, N.; Knoll, M.; Maloy‐Franklin, B.; Melvin, K.; Ruiz‐Pelet, P.; Ozsoy, N.; et al.
Abstract Laboratory studies have shown that small concentrations of silver are effective at inhibiting the growth micro‐organisms through the disruption of important cell structures and processes. The additional ability to incorporate silver into surfaces has increased the usage of silver in the medical field and expanded its use into the consumer market. To understand the impact of increased silver‐containing antimicrobial use, it is important to determine whether silver‐based consumer goods are effective at reducing bacterial populations. Our study examined the antibacterial effectiveness of Agion silver zeolite technology applied to 25 silver‐ and control‐coated door handles across a college campus. Door handles were sampled for 6 week periods in both the fall and spring semester, and bacteria were cultured and enumerated on tryptic soy agar (TSA), MacConkey agar (MAC) and mannitol salt agar (MSA). A significant difference was observed between the bacterial populations isolated from silver‐ and control‐coated door handles after 3 years. However, bacteria were consistently isolated from silver‐coated door handles suggesting that the silver zeolite was only effective against a portion of the bacterial populations, and further studies are necessary to determine the identities of the isolated bacteria and the prevalence of silver resistance. Significance and Impact of the Study There has been a dramatic increase in the use of silver‐containing antimicrobials within the medical and consumer markets despite many concerns on how increased usage will impact the environment. To begin addressing these concerns, it is important to first determine whether the silver‐containing antimicrobials are significantly affecting bacterial populations outside of the controlled laboratory setting. A significant decrease was seen in this study examining the effectiveness of Agion silver zeolite technology applied to door handles across a college campus. Results showed the recovery of a bacterial population on silver‐coated door handles suggesting a bias in the effectiveness of this technology.